Job task analysis of academic librarians assigned in the user services in Pampanga - Marzan, Michelle S. (2009)
Task analysis is a systematic breakdown of a task into its elements. These elements include a detailed task description of both manual and mental activities tasks and element duration, task frequency, task allocation, task complexity, environmental condition, necessary equipment, and any other unique factors involved in or required for one or more humans to perform a given task. The purpose of task analysis is to describe a job as it is actually performed and to understand the job well enough to reliably and accurately define worker requirements. Task analysis is done in many fields such as education, allied medical profession, and engineering, including library science.